PMTCT Service Uptake Among Adolescents and Adult Women Attending Antenatal Care in Selected Health Facilities in Zimbabwe. (1st June 2017) - Musarandega, Reuben; Machekano, Rhoderick; Chideme, Memory; Muchuchuti, Cephas; Mushavi, Angela; Mahomva, Agnes; Guay, Laura
Abstract : Background: Age-disaggregated analyses of prevention of mother-to-child transmission (PMTCT) program data to assess the uptake of HIV services by pregnant adolescent women are limited but are critical to understanding the unique needs of this vulnerable high-risk population. Methods: We conducted a retrospective analysis of patient-level PMTCT data collected from 2011 to 2013 in 36 health facilities in 5 districts of Zimbabwe using an electronic database. We compared uptake proportions for PMTCT services between adolescent (⩽19 years) and adult (>19 years) women. Multivariable binomial regression analysis was used to estimate the association of the women's age group with each PMTCT service indicator. Results: The study analyzed data from 22, 215 women aged 12–50 years (22.5% adolescents). Adolescents were more likely to present to antenatal care (ANC) before 14 weeks of gestational age compared with older women [adjusted relative risk (aRR) = 1.34; 95% confidence interval: 1.22 to 1.47] with equally low rates of completion of 4 ANC visits. Adolescents were less likely to present with known HIV status (aRR = 0.34; 95% confidence interval: 0.29 to 0.41) but equally likely to be HIV tested in ANC. HIV prevalence was 5.5% in adolescents vs 20.1% in adults. While >84% of both HIV-positive groups received antiretroviral drugs for PMTCT, 44% of eligible adolescents were initiated on antiretroviral therapy vs 51.3% of eligible adults, though not statistically significant. Conclusions: Pregnant adolescents must be a priority for primary HIV prevention services and expanded HIV treatment services among pregnant women to achieve an AIDS-free generation in Zimbabwe and similar high HIV burden countries.